Identification of turkey astrovirus and turkey coronavirus in an outbreak of Poult Enteritis and Mortality Syndrome - Villarreal,LYB (2006)
This article reports a survey on turkey astrovirus (TAstV) and turkey coronavirus (TCoV) infections with RT-PCR in 17 turkey flocks affected by acute enteritis and two apparently normal turkey flocks located in the Southeastern region of Brazil by PCR (TAstV and TCoV). Seven out of the 17 affected flocks were positive for TAstV and 14 for TCoV, with seven co-infections. In one of the two apparently normal flocks, a TAstV-TCoV co-infection was found. Although a definitive association of these agents and the signs can not be made, the implications of these findings are discussed.